2009
DOI: 10.2319/0003-3219(2009)079[0436:ioodaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Occurrence of Dental Anomalies Associated with Second-Premolar Agenesis

Abstract: The results provide evidence that agenesis of other permanent teeth, microdontia, deciduous molar infraocclusion, and certain dental ectopias are the products of the same genetic mechanisms that cause second-premolar agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
3
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 5 publications
(6 reference statements)
4
65
3
8
Order By: Relevance
“…It is a condition where mesiodistal crown width of a lateral incisor is smaller compared with the same dimension of the opposite mandibular lateral incisor of the same patient [23]. …”
Section: Methodsmentioning
confidence: 99%
“…It is a condition where mesiodistal crown width of a lateral incisor is smaller compared with the same dimension of the opposite mandibular lateral incisor of the same patient [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Sigler, Baccetti and McNamara Jr 30 (2011) showed that individuals with PDC exhibited significantly higher prevalence of small maxillary lateral incisors (six-fold higher), distoangulation of mandibular second premolars (three-fold higher), and infraocclusion of deciduous molars (two-fold higher) compared with a control group. Other studies verified an increased prevalence of PDC in patients screened for other dental anomalies such as second premolar agenesis, small lateral incisors, infraocclusion of deciduous molars, and enamel hypoplasia 2 , 19 , 29 . Family history has already been identified as a risk factor for PDC and other heritable dental anomalies, as well as the gender bias mentioned 24 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 78%
“…32 Studies that began with an agenesis sample found PDC prevalences of 5.2%-12.6% in the presence of at least one UI2 agenesis 22,23 and 8.1% in the presence of at least one P2 agenesis. 24 All the aforementioned studies do not account for the potential confounding impact of gender. In contrast, the present study examined gender separately and found no interaction between gender and agenesis status.…”
Section: Maxillary Canine Impaction and Agenesis Statusmentioning
confidence: 99%
“…24 In the aforementioned studies, the possible confounding impact of gender on the results was not examined. To our knowledge, no data are available about tooth agenesis concomitant to MCI in Greece.…”
Section: Introductionmentioning
confidence: 98%